Business-IT alignment for Customer Relationship Management : an interpretive qualitative study on the Business value of IT derived by CRM systems of a global institution - Biolchini, Hugo (My University, 2021)
Does the level of business-IT alignment have a positive impact on CRM performance to deliver business value of IT? This research tests this question by using the previous literature and analyzing the model of Batenburg and Versendaal (2004). To answer this, questionnaires, interviews, and observations were conducted in one of the largest renewable energy companies which uses a well-known CRM for its commercial operations. The research model of this study goes further than the previous literature as it includes IT governance and CRM performance between the business and IT alignment and the business value of IT. In accordance with the previous literature, I found that a good level of cohesion between business and IT departments positively impacts CRM performance and enables the company to deliver business value of IT. IT Governance is an important prerequisite for having aligned IT and business departments and therefore also participates in the process of business value of IT creation. In CRM, business-IT alignment can be seen in two different ways. It can be first, a continuous Business-IT alignment that enables the business to improve its selling performance thanks to the CRM platform (information system) and second, a cohesive alignment during a CRM implementation or upgrade project within a company to improve the CRM (IT platform) and improve company's performance over the long term. It is the second type of alignment that is studied as a case study in this thesis, although I assume that the findings should be broadly similar for both types of alignment, it is important to state this. The findings in this thesis corresponded well with the statements of Perreault et al (2007) who mentioned that “CRM improves sales productivity”, and Gellweiler (2017) who described that “higher levels of alignment have positive effects on company performance”.
Keywords: IT Governance, Business-IT Alignment, CRM, Business Value of IT